UNDERSTANDING OF ONE VARIABLE LINEAR INQUIRY TOPIC SMP STUDENTS WITH SPUR APPROACH - Husna Fidda Ro'aini; Abdul Haris Rosyidi (MATHEdunesa, 2020)
Students' understanding can be known based on 4 components, (1) mastery of procedures (skills), (2) the ability to use properties and principles, (3) the ability to use in the context of the problem (uses), and (4) the ability to make representations ( representation). This qualitative research aims to describe students' understanding of the topic of the linear inequality of one variable guided by the 4 components of understanding. The research subjects were 3 students of grade VIII, with details of 1 student indicated to have fulfilled the 4 components of understanding, 1 student indicated to have fulfilled the 3 components of understanding, and 1 student indicated to have fulfilled the 2 components of understanding. Data collection techniques, namely task-based interviews. The results showed that the skill component of each subject mastered the inequality solving procedure, but there were differences in how to simplify, and the accuracy of each subject was also different. In the properties component, each subject provides truth arguments and conclusions in solving problems, but there are differences when identifying problems by using properties related to inequalities. In the use component, each subject is able to solve contextual problems related to inequalities, but there are differences in how to make the mathematical model. In the representation component, each subject has the ability to solve the inequality, but there are differences in representing the results. Keywords: Understanding, one variable linear inequality, and SPUR